The Impact of Ubud Food Festival on the Social and Economic Aspects of the Community in Banjar Penestanan Kaja, Ubud, Bali - Desak Gede Chandra Widayanthi; I Nengah Wirata; Ida Bagus Putu Puja; Desak Putu Candra Dewi (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2022)
Bali is one of the provinces in Indonesia that carry out festival activities in various regions. One of the regular festivals held annually since 2015 is the Ubud Food Festival which is held in Banjar Penestanan Kaja, Ubud District, Gianyar Regency, Bali, Indonesia. Ubud Food Festival is a culinary festival featuring various Indonesian specialties. This research focuses on the social and economic impacts caused by the organizers of the Ubud Food Festival in Banjar Penestanan Kaja Ubud, Gianyar Bali, and expected to be useful for the organizers and the local community of Banjar Penestanan Kaja to find out all kinds of economic and social changes resulting from the implementation of the Ubud Food Festival which has been held for the past five years. The sampling technique in this research is purposive random sampling. Based on the results of the research, it can be concluded that the implementation of an activity or event, especially the implementation of the Ubud Food Festival in Banjar Penestanan Kaja, has impacted the social and economic aspects for the community. Positive impacts from social aspects are: Ubud Food Festival is a place to socialize and exchange experiences between the people of Banjar Penestanan Kaja. raises awareness of the local community, fosters the creativity of the people of Banjar Penestanan Kaja, and makes people feel more special and satisfied. The positive impact from the economic aspect are: Ubud Food Festivals are directly or indirectly a promotional medium for Banjar Penestanan Kaja as a venue for events and also as a tourist destination, increasing income, especially in the tourism sector, increasing the employment opportunities during the Ubud Food Festival. While, the negative impact of the social aspect is the influx of culture brought by tourists visiting Banjar Penestanan Kaja causes the loss of identity and cultural authenticity in Banjar Penestanan Kaja, and the negative impact from the economic aspect is people tend to rely on the tourism sector as a livelihood.